Development of methodological approach for structure formation of the tourist trains - Марценюк, Лариса Володимирівна (Technology audit and production reserves, 2016)
Challenges and future directions of development of tourism in Ukraine, as well as the experience of travelling by rail are overviewed. Expediency of use of rail transport for implementation of new services – travelling by train – is proved to increase the competitiveness of rail transport, development of domestic and inbound tourism in Ukraine, creating a positive image of the state abroad. The condition of modern tourist and transport infrastructure is analyzed. For the first time in Ukraine a methodical approach to build different variants of the structure of tourist train is developed depending on the class, length of trip, belonging to a cruise or viewing tourism, meal scheme and the number of seats in the train, which will calculate the required number of carriages of 1st and 2nd classes, dining carriages, casino-carriages, total amount of tourist carriages and their cost. The development of railway tourism in Ukraine will contribute to the restoration of architectural monuments, tourist sites, renovation of passenger railway carriages. In addition, expanding the range and level of services will increase the competitiveness of rail transport, create a positive image in the international arena, attract additional tourists, and as a result, receive regular replenishment of different budgets.